Building a Generation with Integrity: Internalizing Anti-Corruption Values Through the Islamic Religious Education Curriculum - Arsyad, Muhammad; Lutfi, Mukhtar; Yahdi, Muh. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2026)
This study aims to uncover the internalization of anti-corruption educational values ​​in Islamic Religious Education subjects at SMAN 3 Pangkep. The type of research used is qualitative research. Data collection methods in this study were collected using three methods, namely through observation, interviews, documentation. Data analysis techniques used include data reduction, data presentation, and data verification. The results of this study indicate that the values ​​of Anti-Corruption Education in Islamic Religious Education subjects at SMAN 3 Pangkep are: the value of honesty and the value of discipline. The instillation of Anti-Corruption Educational values ​​is carried out by emphasizing these values ​​when explaining, providing insight related to anti-corruption materials to students in between learning materials as an introduction to the hidden curriculum. The implications of this study indicate that the implementation of Islamic Religious Education at SMAN 3 Pangkep is effective in instilling the values ​​of honesty, discipline, and anti-corruption behavior. This success is supported by the active role of teachers as role models, varied and interactive learning methods, the support of a conducive school environment, and family involvement. Abstrak: Penelitian ini bertujuan untuk mengungkap internalisasi nilai-nilai pendidikan anti korupsi dalam mata pelajaran Pendidikan Agama Islam di SMAN 3 Pangkep. Jenis penelitian yang digunakan ialah penelitian kualitatif. Metode pengumpulan data dalam penelitian ini dikumpulkan dengan menggunakan tiga metode, yaitu melalui Observasi, Wawancara, Dokumentasi. Teknik analisis data yang dipakai meliputi reduksi data, penyajian data dan verifikasi data. Hasil penelitian ini menunjukkan bahwa Nilai-nilai Pendidikan Anti Korupsi dalam mata pelajaran Pendidikan Agama Islam di SMAN 3 Pangkep yaitu: nilai kejujuran dan nilai kedisiplinan. Penanaman nilai-nilai Pendidikan Anti Korupsi dilakukan dengan menekankan nilai-nilai tersebut ketika menjelaskan, memberikan wawansan terkait materi-materi anti korupsi kepada peserta didik di sela-sela materi pembelajaran sebagai pengantar yang bersifat hidden curikulum (kurikulum tersembunyi). Implikasi dari penelitian ini menunjukkan bahwa penerapan Pendidikan Agama Islam di SMAN 3 Pangkep efektif menanamkan nilai-nilai kejujuran, kedisiplinan, dan perilaku anti korupsi. Keberhasilan ini ditunjang oleh peran aktif guru sebagai teladan, metode pembelajaran yang variatif dan interaktif, dukungan lingkungan sekolah yang kondusif, serta keterlibatan keluarga.